2020
DOI: 10.1111/inm.12781
|View full text |Cite
|
Sign up to set email alerts
|

Training mental health peer support training facilitators: a qualitative, participatory evaluation

Abstract: The facilitator’s training for peer support workers in mental health course was a recovery‐based initiative addressed to professionalize peer support in Catalonia, Spain. Our aim was to elicit participants’ motivations, significant learnings, and opinions regarding the training programme. A qualitative approach was used through content and thematic analyses of the course contents and participation narratives. The motivations to attend the course were helping others, learning, and supporting the implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
0
18
0
2
Order By: Relevance
“…Health status, which usually includes mental health and physical health, is a crucial indicator of successful aging ( 63 , 64 ). For mental health, it was measured using the abbreviated 12-item Center for Epidemiologic Studies Depression scale (CES-D) ( 65 ).…”
Section: Methodsmentioning
confidence: 99%
“…Health status, which usually includes mental health and physical health, is a crucial indicator of successful aging ( 63 , 64 ). For mental health, it was measured using the abbreviated 12-item Center for Epidemiologic Studies Depression scale (CES-D) ( 65 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nine studies reported general improvements in knowledge and skills from participating in training, immediately post-training (Bentley, 2000;Cleary et al, 2009;Compton et al, 2014;Hoagwood et al, 2018;Horwitz et al, 2020;Sanchez-Moscona & Eiroa-Orosa, 2021;Simpson et al, 2014) and at follow-up (Hegedüs et al, 2016;King et al, 2009). Across ten studies, trainees developed program-specific skills during the course of training participation (Blixen et al, 2015;Treloar et al, 2012;Willging et al, 2016), immediately after training (Crisanti et al, 2016;Gerry et al, 2011;Joo et al, 2018;Meehan et al, 2002;Weeks et al, 2006) and at follow-up (Rodriguez et al, 2011).…”
Section: Professional Developmentmentioning
confidence: 99%
“…In five training programs in which it was assessed, the trainings were regarded as useful or beneficial by participants (Atif et al, 2019;Cleary et al, 2009;Deren et al, 2012;Franke et al, 2010;King et al, 2009), and content was appropriate and useful (Bentley, 2000;Franke et al, 2010;Meehan et al, 2002;Sanchez-Moscona & Eiroa-Orosa, 2021;Stockmann et al, 2019). In seven studies, support from other trainees and coaches/supervisors (Colon et al, 2010;King et al, 2009;Simpson et al, 2014;Stockmann et al, 2019;Tse et al, 2014;Willging et al, 2016), and family and service users (Tse et al, 2014) were seen as motivating factors.…”
Section: Training Satisfaction/utilitymentioning
confidence: 99%
See 2 more Smart Citations